Whole Genome Sequencing and Comparative Genomic Analysis Reveal Allelic Variations Unique to a Purple Colored Rice Landrace (Oryza sativa ssp. indica cv. Purpleputtu) - Lachagari, V. B. Reddy; Gupta, Ravi; Lekkala, Sivarama Prasad; Mahadevan, Lakshmi; Kuriakose, Boney; Chakravartty, Navajeet; Mohan Katta, A. V. S. K.; Santhosh, Sam; Reddy, Arjula R.; Thomas, George (Frontiers in Plant Science, 2019)
Purpleputtu (Oryza sativa ssp. indica cv. Purpleputtu) is a unique rice landrace from southern India that exhibits predominantly purple color. This study reports the underlying genetic complexity of the trait and associated domestication and de-domestication processes during its coevolution with present day cultivars. Along-with genome level allelic variations in the entire gene repertoire associated with the purple, red coloration of grain and other plant parts. Comparative genomic analysis of the whole genome sequence of Purpleputtu (PP) revels total of 3,200,951 variants including 67,774 unique variations were observed in PP when compared with ‘a panel of 108 rice lines’. Multiple sequence alignment uncovered a 14bp deletion in Rc (Red colored, a transcription factor of bHLH class) locus of PP, a key regulatory gene of anthocyanin biosynthetic pathway. Interestingly, this deletion in Rc gene is a characteristic feature of the present-day white pericarped rice cultivars. Phylogenetic analysis of Rc locus revealed a distinct clade showing proximity to the progenitor species Oryza rufipogon and O. nivara. In addition, PP genome exhibits a well conserved a 4.5Mbp region on chromosome 5 that harbors several loci associated with domestication of rice. Further, PP showed 1,387 unique SNPs compared to 3,023 lines of rice (SNP-Seek database). The results indicate that PP genome is rich in allelic diversity and can serve as an excellent resource for rice breeding for a variety of agronomically important traits such as disease resistance, enhanced nutritional values, stress tolerance and protection from harmful UV-B rays.